Job Satisfaction of Women Teachers in Matriculation Schools: A Study with Reference to Sivakasi, Tamil Nadu - Selvakumar, M.; Dhanalakshmi, V. (Prabandhan: Indian Journal of Management, 2012)
The children are called the future of the nation, and the teachers are the nation builders. Teaching is the biggest source of employment for women in the formal sector. Teachers play a vital role in the all round development of the younger generation. Teacher’s values, attitudes and ideas about teaching greatly influence the children’s future. It is the teaching community and the education system of a country that plays a crucial role in the process of human resource development, which is vital for peace, prosperity and the overall progress, including mental, physical, moral and spiritual development of a society or nation. Job satisfaction is one’s attitude towards his job (positive or negative). Satisfaction with work and the work environment is the basic constituent of an employee’s job satisfaction. The education sector is one of the largest employing sectors of the Indian economy. In order to know the level of job satisfaction of women teachers in matriculation schools in Sivakasi, Tamil Nadu, the present research was carried out.